Enhancing jackfruit’s bioactive properties through SCOBY fermentation: implications for cosmeceuticals - Aziz Norhazniza,; Koh, Soo Peng; Norefrina Shafinaz Md Nor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigated the bio-processing technique of fermenting jackfruit pulp (JP) and leaves (JL) using a symbiotic culture of bacteria and yeast (SCOBY) to enhance their bioactive properties. To assess the nutritional value of the jackfruit extracts, the phenolic and organic acid compositions were determined. The extracts were also evaluated for their anti-inflammatory properties by measuring their ability to suppress the production of nitric oxide (NO) in response to bacterial lipopolysaccharide (LPS) stimulation in RAW 264.7 macrophage cell line. Furthermore, the inhibitory effects of the extracts on elastase and tyrosinase, enzymes associated with skin aging, were assessed. The fermentation process led to increased phenolic content. This included vitexin, salicylic acid, and benzoic acid. Acetic acid was the most abundant organic acid detected after fermentation, with concentrations ranging from 16.0 to 16.1 mg/mL. Additionally, the fermented extracts exhibited elevated levels of other beneficial organic acids such as citric and quinic acid. The study demonstrated significant reductions in nitrite formation in LPS-stimulated RAW 264.7 cells treated with jackfruit extracts. This finding suggests that the fermented extracts can effectively suppress NO production in a concentration-dependent manner. Among the fermented extracts, JL exhibited the highest inhibition of NO production at a concentration of 19.5%, resulting in a 42.23% reduction. Moreover, fermentation enhanced the inhibitory effects of the jackfruit extracts on elastase and tyrosinase, with inhibition rates ranging from 82.3% to 95.4%. Overall, the findings suggest that fermented jackfruit exhibits increased levels of phytochemical compounds and holds promise as a natural and beneficial ingredient in cosmeceutical products, offering anti-inflammatory and skin-aging benefits.